Alpha-Lipoic Acid in Diabetic Peripheral Neuropathy: Addressing the Challenges and Complexities Surrounding a 70-Year-Old Compound - Iliya Mangarov; Yulian Voynikov; Valentina Petkova; Simeon Iliev; Ivanka Kostadinova; Lyubomir Marinov; Irina Nikolova (Current Issues in Molecular Biology, 2025)
Alpha-lipoic acid (ALA, also known as thioctic acid) was discovered nearly 90 years ago and began to be used in clinical practice in the late 1950s. Numerous nonclinical and clinical studies have investigated ALA for treating diabetic peripheral neuropathy (DPN) and various other diseases. The rising global prevalence of DPN necessitates timely treatment; however, there is currently no effective cure. Current guideline-recommended therapies for DPN provide symptom relief rather than modifying the disease. Among the pathogenesis-oriented therapies, ALA holds a unique position as a universal antioxidant, essential for every cell in the body. This review highlights the ongoing issues and challenges in using ALA to treat DPN. While confronting a complex disease with poorly understood pathophysiology, we also have an endogenous substance with pleiotropic effects on all cells in the human body. It becomes clear that this is a highly multifactorial process that will likely never be precisely defined. This does not diminish the significance of ALA in treating DPN but underscores the need for a deeper understanding of when to start therapy, dosage, duration, and monitoring. In this comprehensive review, we evaluate the achievements of the past 70 years and highlight gaps in ALA’s role in treating DPN.